(3TQM bUjOI GdHGFjI ddSjO GdMejQis - (3dCHi GdbGSe Ydj Hf GdMSjfj Hf ehSi GdTQja GdeQJVis; (3CHh gGTe ESeGYjd Hf eMeO Hf eaQZ, GdMejQj,J (B173 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3SCd GdCSJGP GdaGVd CHh GdMSf Ydi Hf TgjRh, COGe Gddg YRg s
(3BNQgG (B:s
(3hYfOg Yde GdcJGH hYde eG de jcJH (B: (3ajMJed CeQjf CMOgeG Cf jQjO HGdcJGH cJHg ai GddhM GdeMahX hGdhLg GdCNQ jQjO HGdcJGH GdbQBf JeJ GdbUjOI HTQMgG s
(3HBNQ UaGJgG JYbjHg hHBNQgG dMbGf ef UfY GdTGQMs
(3jJVefGf CNHGQ GdSjO GdMejQis
(3efbhdGf Yf fSNJjf bOjeJjfs
(3fSNI KGfjI hjJab ai CNQgG eY BNQ GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdCOHs